(3bUjOI HGfJ SYGOs - (3cYH Hf RgjQ Hf CHj Sdej,J (B26 (3g` s
(3ChdgG (B:s
(3HGfJ SYGO abdHi Gdjhe eHJhd eJje EKQgG de jaO ecHhd heG SYGO ZOGI GdHjf EP QMdJ EdG CZf ZVjV GdWQa ecMhd s
(3BNQgG (B:s
(3dGjbY GdWYf EdG ai fMhQge heGdge Yf MjGV GdehJ Jgdjd s
(3GdfSNI HgG MhGTs
(3YOO CHjGJ GdbUjOI (B58 (3HjJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B81 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B144s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1329s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs